Compact multi‐frequency system design for SWIPT applications. Issue 6 (21st March 2021) - Dautov, Kassen; Hashmi, Mohammad; Nauryzbayev, Galymzhan; Nasimuddin, N.; Chaudhary, Muhammad A.
Abstract: The potential advantages of simultaneous wireless information and power transfer (SWIPT) applications have necessitated innovations in the associated circuits and systems. This article, therefore, explores the concept of cascaded resonators, for the first time, in the design of a compact‐size defected ground structure (DGS)‐based tri‐band wireless power transfer (WPT) system to advance the SWIPT technology. The design is augmented with a systematic design procedure that is preceded by the development of a new double‐elliptic DGS‐based tri‐band resonator. Initially, the analysis of the proposed resonator is performed to identify the impact of defect size on the bandwidth. Subsequently, the resonators are cascaded to achieve a tri‐band functionality and then utilized in the design of WPT. The designed WPT operates at 0.3, 0.5, and 0.9 GHz, and takes a compact size of 39 × 13 mm 2 . The measurement of the realized WPT with the transmitter and receiver, separated by the distance of 10 mm, provides an efficiency of around 60% at all three bands with the figure of merit values of about 0.5. Furthermore, the proposed design achieves a bandwidth of more than 3 MHz bandwidth at the frequencies corresponding to communication standards.